Towards a new development paradigm in twenty-first century China : economy, society and politics - Florence, Éric.; Defraigne, Pierre (New York : Routledge, 2013)
"This book argues that the current state of China requires an important paradigm shift in the way the party-state manages the country's development, and goes on to assess the fitness of the party-state for implementing such a paradigm shift and the likelihood of the party-state bringing this about. It brings together an examination of the very latest situation in a range of key areas where current developments have the potential to undermine substantially the status quo, areas such as the recent economic crisis and the resulting economic slowdown, increasing labour unrest, mounting calls for social justice, worsening urban-rural disparity, the urgent need to implement social welfare programmes, the rise of civil society, and the impact of new media. Overall, the book provides a thorough appraisal of the difficulties which China currently faces."--
pt. I. Reorientation of the Chinese growth model -- pt. II. Recent policy shifts in the fields of labour and welfare -- pt. III. The party-state and Chinese society : contention, accommodation and collaboration.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: China -- Economic policy -- 2000-; China -- Economic conditions -- 2000-; China -- Social policy -- 21st century; China -- Politics and government -- 2002-; Electronic books